Characterization of the Poplar Pan-Genome by Genome-Wide Identification of Structural Variation. (7th August 2016) - Pinosio, Sara; Giacomello, Stefania; Faivre-Rampant, Patricia; Taylor, Gail; Jorge, Veronique; Le Paslier, Marie Christine; Zaina, Giusi; Bastien, Catherine; Cattonaro, Federica; Marroni, Fabio; Morgante, Michele
Abstract: Many recent studies have emphasized the important role of structural variation (SV) in determining human genetic and phenotypic variation. In plants, studies aimed at elucidating the extent of SV are still in their infancy. Evidence has indicated a high presence and an active role of SV in driving plant genome evolution in different plant species. With the aim of characterizing the size and the composition of the poplar pan-genome, we performed a genome-wide analysis of structural variation in three intercrossable poplar species: Populus nigra, Populus deltoides, and Populus trichocarpa . We detected a total of 7, 889 deletions and 10, 586 insertions relative to the P. trichocarpa reference genome, covering respectively 33.2 Mb and 62.9 Mb of genomic sequence, and 3, 230 genes affected by copy number variation (CNV). The majority of the detected variants are inter-specific in agreement with a recent origin following separation of species. Insertions and deletions (INDELs) were preferentially located in low-gene density regions of the poplar genome and were, for the majority, associated with the activity of transposable elements. Genes affected by SV showed lower-than-average expression levels and higher levels of d N /d S, suggesting that they are subject to relaxed selective pressure or correspond to pseudogenes. Functional annotation of genes affected by INDELs showed over-representation of categories associated with transposable elements activity, while genes affected by genic CNVs showed enrichment in categories related to resistance to stress and pathogens. This study provides a genome-wide catalogue of SV and the first insight on functional and structural properties of the poplar pan-genome.